2012
DOI: 10.1002/mus.23426
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve ultrasound as a screening tool in carpal tunnel syndrome: Correlation of cross‐sectional area measures with electrodiagnostic abnormality

Abstract: Median nerve ultrasound is a highly sensitive screening tool for EDx abnormality, but it cannot determine severity. This may lead to changes in the current standards for evaluating CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
167
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(183 citation statements)
references
References 44 publications
9
167
2
5
Order By: Relevance
“…Some have found that CSA increased from mild to moderate severity (Chen et al, 2011), others have reported that ultrasonography can be complementary but not conclusive in the classification of CTS severities (Abrishamchi et al, 2015). On the other hand, in the study of Mhoon et al (2012), no significant correlation was demonstrated between ultrasound parameters and electrophysiological severity and concluded that ultrasound cannot determine severity.…”
Section: Discussionmentioning
confidence: 92%
“…Some have found that CSA increased from mild to moderate severity (Chen et al, 2011), others have reported that ultrasonography can be complementary but not conclusive in the classification of CTS severities (Abrishamchi et al, 2015). On the other hand, in the study of Mhoon et al (2012), no significant correlation was demonstrated between ultrasound parameters and electrophysiological severity and concluded that ultrasound cannot determine severity.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, whereas the ERK/Elk-1, JAK/STAT, and AKT/ CREB pathways have all been correlated to neuroprotection, it is today widely admitted that IGF-1-mediated neuroprotection occurs through activation of the AKT/CREB pathway (D'Mello et al, 1997;Párrizas et al, 1997;Yadav et al, 2005). Furthermore, in the specific case of cerebellar granule neurons, IGF-1-induced neuroprotection results from both the activation of AKT and the inhibition of MEK-ERK1/2 through the AKT pathway (Subramaniam et al, 2005). Similarly, the neuroprotection induced by IGF-1R reduction in SMA spinal cords, as evidenced by the relative persistence of the motor neuron population and the reduced activation of caspase-3, might result from both an increased SMN protein expression and the presence of the two powerful antiapoptotic molecules, AKT and CREB, at the activated state.…”
Section: Discussionmentioning
confidence: 99%
“…MN-1 (Motoneuron-1) cells have been derived from the spinal cords of E18 control mice and immortalized (Salazar-Grueso et al, 1991). These cells only harbor the two alleles of the murine Smn genes.…”
Section: Methodsmentioning
confidence: 99%
“…In a hand with carpal tunnel syndrome (CTS), Ultrasonography can show the enlarged median nerve just proximal to the carpal tunnel [1]. In open carpal tunnel release surgery, the enlarged median nerve is recognized as a pseudoneuroma.…”
Section: Introductionmentioning
confidence: 99%